2008
DOI: 10.1101/gr.078246.108
|View full text |Cite
|
Sign up to set email alerts
|

Mouse let-7 miRNA populations exhibit RNA editing that is constrained in the 5′-seed/ cleavage/anchor regions and stabilize predicted mmu-let-7a:mRNA duplexes

Abstract: Massively parallel sequencing of millions of <30-nt RNAs expressed in mouse ovary, embryonic pancreas (E14.5), and insulin-secreting beta-cells (␤TC-3) reveals that ∼50% of the mature miRNAs representing mostly the mmu-let-7 family display internal insertion/deletions and substitutions when compared to precursor miRNA and the mouse genome reference sequences. Approximately, 12%-20% of species associated with mmu-let-7 populations exhibit sequence discrepancies that are dramatically reduced in nucleotides 3-7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
86
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 46 publications
11
86
0
1
Order By: Relevance
“…Several recent reports have shown that in both animals (humans, mice, D. melanogaster, and Caenorhabditis elegans) and plants (Arabidopsis thaliana, Oryza sativa, and Populus trichocarpa) miRNAs exhibit heterogeneous 59 and 39 ends, and post-transcriptional nontemplate 39 end additions of uridines or adenosines (Li et al 2005;Landgraf et al 2007;Ruby et al 2007;Azuma-Mukai et al 2008;Morin et al 2008;Reid et al 2008;Seitz et al 2008;Ebhardt et al 2009;Lu et al 2009). Although the biological relevance of these miRNA isoforms, or isomiRs, has been questioned, there is evidence in A. thaliana that terminal nucleotide additions occur after Dicer processing of the miRNA precursor (Li et al 2005), and that some variants are differentially loaded into Argonautes (Seitz et al 2008;Ebhardt et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have shown that in both animals (humans, mice, D. melanogaster, and Caenorhabditis elegans) and plants (Arabidopsis thaliana, Oryza sativa, and Populus trichocarpa) miRNAs exhibit heterogeneous 59 and 39 ends, and post-transcriptional nontemplate 39 end additions of uridines or adenosines (Li et al 2005;Landgraf et al 2007;Ruby et al 2007;Azuma-Mukai et al 2008;Morin et al 2008;Reid et al 2008;Seitz et al 2008;Ebhardt et al 2009;Lu et al 2009). Although the biological relevance of these miRNA isoforms, or isomiRs, has been questioned, there is evidence in A. thaliana that terminal nucleotide additions occur after Dicer processing of the miRNA precursor (Li et al 2005), and that some variants are differentially loaded into Argonautes (Seitz et al 2008;Ebhardt et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Global and unequivocal identification of RNA editing targets represents a critical first step in further understanding this post-transcriptional modification. This calls for complete information on whole-genome and transcriptome sequences from the same individual, so as to exclude polymorphisms and mutations among populations, as well as experimental approaches with the necessary high-throughput sequencing and base resolution 13,14 . Whole-transcriptome deep-sequencing technologies (e.g., RNASeq) [15][16][17] , with their capacity to simultaneously assay the entire transcriptome, represent an excellent choice of tool in this regard.…”
mentioning
confidence: 99%
“…In addition, A-to-I editing can play important roles in regulating gene expression , such as by altering alternative splicing (Rueter et al 1999;Laurencikiene et al 2006;Schoft et al 2007), miRNA sequences (Kawahara et al 2007(Kawahara et al , 2008Reid et al 2008;Dupuis and Maas 2010), or miRNA target sites in the mRNA (Liang and Landweber 2007;Borchert et al 2009). Other types of putative RNA editing events are also known, for example, C-to-U editing and U-to-C and G-to-A conversions (Nutt et al 1994;Sharma et al 1994;Villegas et al 2002;Klimek-Tomczak et al 2006), but with much less prevalence.…”
mentioning
confidence: 99%